Advances in the adsorption of heavy metal ions in water by UiO-66 composites - Yuanhang Lei; Jiangqin Xie; Wenxuan Quan; Qi Chen; Xingyu Long; Anping Wang; Anping Wang (Frontiers in Chemistry, 2023)
The innovative adsorbents known as the Metal-organic Framework (MOFs) had a high specific surface area, various structural types, and good chemical stability. MOFs have been produced through hydrothermal, mechanochemical, microwave-assisted, gelation, and other synthesis methods, and the solvothermal process is one of them that researchers frequently utilize. The UiO materials have a more comprehensive application potential than different subtypes of MOFs among the numerous MOFs that have been synthesized. The synthesis of MOFs and their composites, as well as the adsorption characteristics of UiO materials in the adsorption of various heavy metal ions, have all been examined and summarized in this study.